Studies of a spring phytoplankton bloom in an enclosed experimental ecosystem. I. Biochemical changes in relation to the nutrient chemistry of water - Morris, R.J.; McCartney, M.J.; Robinson, G.A. (Journal of experimental marine biology and ecology, 1983)
A spring bloom of diatoms which occurred in large enclosed ecosystem bags at Loch Ewe, Scotland, during 1980, has been the subject of a chemical study. Changes observed in the general biochemical composition of the diatoms during the bloom are compared with the species distribution and changes in the nutrient chemistry of the bag water. The results indicate that major changes in cell biochemistry are associated with the growth, development, and decay of a diatom bloom, particularly if one or more nutrients become limiting.